Determination of the home advantage in handball Olympic Games and European Championships - Gutiérrez Aguilar, O.; Fernández Romero, J. J.; Saavedra Garcia, M. (Journal of Human Sport & Exercise, 2014)
Home advantage (HA) has typically been focused in competitions in which the same number of home games and away games are played, but it should be noted that there are other competitions that take place at the home of only one organizer. In this study, 2,758 games of handball were analyzed. The variables registered were the number of games won, the number of games drawn, the number of games lost, the number of goals scored, the number of goals against and the gender of the competitors. The significance of the level of advantage in playing at home was calculated for the variable of points obtained, assuming the null hypothesis that playing at home has no advantage. The Wilcoxon signed rank was used to contrast home advantage signification. The advantage of playing at home and the advantage of playing away in male and female competitions were compared using the Mann-Whitney test. The significance of the difference between the goals (both scored by and scored against) when a team played at home or played away from home was determined using t tests. Pearson and Spearman bivariate correlations were used to establish the level of association between the classification of a team and the number of points obtained as a result of the advantage of playing at home. No significant advantage to playing at home in the Olympic Games or European Championships was found for either gender. However, a direct association exists between playing at home and the points obtained in a competition. There is also a significant inverse association between playing at home and the final classification of a team.